Produksi Pesan Publisitas Workshop Pesantren Kilat Copywriting pada Telegram - Luthfi Apriliasari; Neni Yulianita; Maman Suherman (Jurnal Inovasi Komunikasi, 2023)
Abstract: The Copywriting Flash Islamic Boarding School Workshop is a training in the field of copywriting which is held online via telegram. The purpose of holding this workshop is especially for SMEs to be able to make good communication for the business/brand they manage. The implementation of this workshop has been held stepping on the 6th series. In promotional activities using publicity, one of the messages using storytelling. In the marketing approach, storytelling is unique because it can give birth to the human spirit. The product is no longer something tangible that is being sold, but a story in it. Brands are packaged and immersed to become an integral part of such an interesting story. So the purpose of this study is to find out the process of producing publicity messages from the Copywriting Islamic Boarding School Workshop on Telegram using storytelling. To analyze these problems, the researcher used a case study as a scalpel. Then this phenomenon is photographed through the lens of message design logic theory and narrative paradigm theory. This research method uses a constructivist paradigm and a qualitative research approach. The results of this study indicate that the publicity message produced at the initial stage is the introduction of the target audience and the brand as the key. The preparation of this publicity message is informative and persuasive which is implemented into storytelling. The use of storytelling in fact gave birth to several impacts such as the physical impact, the human spirit impact and the emotional impact Abstrak: Workshop Pesantren Kilat Copywriting ialah sebuah pelatihan dalam bidang ilmu copywriting yang diselenggarakan secara online melalui telegram. Tujuan digelarnya workshop ini khususnya bagi para UKM agar mampu membuat komunikasi yang baik untuk bisnis/brand yang dikelolanya. Penyelenggaraan workshop ini telah digelar menginjak seri ke-6. Pada aktivitas promosinya menggunakan publisitas yang salah satu pesannya menggunakan storytelling. Pada pendekatan pemasaran, storytelling menjadi unik karena mampu melahirkan sisi human spirit. Produk bukan lagi sesuatu yang tangible yang dijual, melainkan sebuah cerita di dalamnya. Brand dikemas dan dibenamkan menjadi bagian integral cerita yang begitu menarik. Maka tujuan dari penelitian ini adalah untuk mengetahui proses produksi pesan publisitas Workshop Pesantren Kilat Copywriting Pada Telegram menggunakan storytelling. Untuk menganalisa permasalahan tersebut maka peneliti menggunakan studi kasus sebagai pisau bedahnya. Kemudian fenomena tersebut dipotret dengan kacamata teori logika desain pesan dan teori paradigma naratif. Metode penelitian ini menggunakan paradigma konstruktivistik dan pendekatan penelitian kualitatif. Hasil penelitian ini menunjukan bahwasannya pesan publisitas diproduksi pada tahap mulanya ialah pengenalan khalayak sasaran dan brand sebagai kuncinya. Penyusunan pesan publisititas ini bersifat informatif dan persuasif yang diimplementasikan ke dalam storytelling. Penggunaan storytelling ini nyatanya melahirkan beberapa dampak seperti the physical impact, the human spirit impact dan the emotional impact